Post-artificial insemination supplementation with calcium salts of soybean oil influences pregnancy establishment factors in Bos indicus beef cows - Cipriano, R. S.; Cooke, R. F. [UNESP]; Rodrigues, A. D. [UNESP]; Silva, L. G. T. [UNESP]; Bohnert, D. W.; Marques, R. S.; Vasconcelos, J. L. M. [UNESP]; Pires, A. V.; Cerri, R. L. A. (Amer Soc Animal Science, 2016)
The objective of this experiment was to compare hormonal, uterine, and conceptus factors associated with pregnancy establishment in Bos indicus beef cows supplemented or not with Ca salts of soybean oil (CSSO) for 21 d beginning after timed AI. One hundred lactating multiparous Nelore cows were allocated to 20 groups of 5 cows/group and timed inseminated on d 0 of the experiment. After AI, groups were randomly assigned to receive (as-fed basis) 100 g of protein-mineral mix + 100 g of ground corn per cow per day, in addition to 1) 100 g/cow daily of CSSO (n = 10) or 2) 100 g/cow daily of kaolin (CON; rumen-inert indigestible substance; n = 10). Groups were maintained in 4 Panicum maximum pastures (5 groups from the same treatment within each pasture) with ad libitum access to forage. Groups were segregated daily and individually offered treatments from d 0 to 21. Blood samples were collected and transrectal ultrasonography was performed to verify ovulation and corpus luteum (CL) volume immediately before AI (d 0) and on d 7 and 15. After ultrasonography on d 15, 60 cows (30 cows/treatment and 3 cows/group) diagnosed without the presence of a CL on d 0 but with a CL greater than 0.38 cm3 in volume on d 7 and 15 were assigned to conceptus collection via transcervical flushing with PBS followed by endometrial biopsy in the uterine horn ipsilateral to the CL. Additional blood samples were collected for wholeblood RNA extraction (d 20), and pregnancy status was verified by transrectal ultrasonography (d 30) in cows not assigned to conceptus collection. Cows receiving CSSO had greater (P <= 0.04) mean plasma linoleic acid concentration, plasma linoleic: linolenic acid ratio, plasma progesterone (P4) concentration, and CL volume during the experiment compared with CON cows. Moreover, CSSO supplementation increased (P <= 0.04) length and mRNA expression of prostaglandin E synthase and interferon-tau by the conceptus as well as blood mRNA expression of interferon-stimulated genes on d 20 in gestating cows. No treatment differences were detected (P >= 0.30) for endometrial mRNA expression of prostaglandin E synthase and cyclooxygenase-2. In summary, post-AI CSSO supplementation to B. indicus beef cows increased plasma concentration of linoleic acid and enhanced pregnancy establishment factors, which included CL development and plasma P4 concentration, conceptus growth, and mRNA expression of interferon-tau as well as blood mRNA expression of interferon-stimulated genes.
Keywords: beef cows; calcium salts of soybean oil; gene expression; interferon-tau; pregnancy; progesterone